Monomer composition for preparing superabsorbent polymer
By using monomer compositions of acrylic monomers with acidic groups and other additives, combined with heat and/or light polymerization reaction, the problems of insufficient absorption rate and deterioration of surface tension of existing superabsorbent polymers are solved, and the problem of insufficient absorption rate and deterioration of surface tension is achieved. Fast absorption and high gel strength effects.
Patent Information
- Application Number
- CN202480003052.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-03-03
- Filing Date
- 2024-03-04
- Publication Date
- 2025-02-07
AI Technical Summary
In the existing method of preparing superabsorbent polymers, bubbles produced by the foaming agent disappear before the monomer polymerization, and sufficient pores cannot be formed, resulting in insufficient absorption speed, and the use of bubble stabilizers will lead to surface tension deterioration.
The monomer composition containing acrylic monomers with acid groups, crosslinking agents, clays, carbonate foaming agents and polymerization initiators is used, and normalized coagulation is controlled by polymerization reactions of heat and/or light. The glue spot is between 0.01 and 0.1 to improve gel strength and absorption speed.
Fast absorption speed and excellent gel strength are achieved, bubble loss generated by the foaming agent and excellent surface tension are maintained.
Smart Images

Figure BDA0005197845120000231 
Figure BDA0005197845120000241
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of Korean Patent Application No. 10-2023-0028619 filed on March 3, 2023, and Korean Patent Application No. 10-2024-0030792 filed on March 4, 2024, in the Korean Intellectual Property Office, the disclosures of which are incorporated herein in their entirety by reference. Technical Field
[0003] The present invention relates to monomer compositions for preparing superabsorbent polymers. Background Art
[0004] Superabsorbent polymer (SAP) is a synthetic polymer material that can absorb 500 to 1000 times its own weight in water. It was first commercialized as a sanitary product. In addition to being used as sanitary products such as diapers and sanitary pads for children, it is currently widely used as a soil water retention material, a waterproof material for civil engineering and construction, a sheet for seedling cultivation, a preservative in the food distribution field, a dressing material, etc.
[0005] Superabsorbent polymers are generally prepared by neutralizing water-soluble unsaturated ethylenic monomers with alkali metal salts (eg, sodium salts) or basic compounds (eg, caustic soda), and then adding a crosslinking agent, a polymerization initiator, etc. to polymerize the resulting monomer composition.
[0006] As a method for improving the absorption speed of a super absorbent polymer, a method is known in which a foaming agent is added to perform polymerization while forming bubbles in a monomer composition, thereby forming a porous structure in the super absorbent polymer to increase the surface area.
[0007] However, in the case of a method for preparing a superabsorbent polymer using an existing foaming agent, bubbles generated by the foaming agent disappear before the monomer is polymerized, so sufficient pores cannot be formed in the superabsorbent polymer. Therefore, a method of using a bubble stabilizer together with a foaming agent to reduce bubble loss has been proposed, but there is a problem that the surface tension of the superabsorbent polymer is deteriorated due to the bubble stabilizer.
[0008] Therefore, there is a need to develop a superabsorbent polymer that exhibits a rapid absorption speed without deteriorating properties such as surface tension. Summary of the invention
[0009] [Technical issues]
[0010] An object of the present invention is to provide a monomer composition for preparing a superabsorbent polymer, which can prepare a superabsorbent polymer having a fast absorption speed and excellent gel strength.
[0011] [Technical solution]
[0012] One embodiment of the present invention provides a monomer composition for preparing a superabsorbent polymer, comprising:
[0013] an acrylic monomer having an acidic group at least part of which is neutralized; a crosslinking agent; clay; a carbonate foaming agent; and a polymerization initiator,
[0014] Wherein, when the monomer composition for preparing a super absorbent polymer is irradiated with heat and / or light to perform a polymerization reaction, the normalized gel point represented by the following formula 1 is 0.01 to 0.1:
[0015] [Formula 1]
[0016] Normalized gel point = gel point (seconds) / total polymerization time (seconds)
[0017] In Formula 1, the gel point is the polymerization time at the intersection of a storage modulus graph of the monomer composition for preparing the super absorbent polymer according to polymerization time and a loss modulus graph of the monomer composition for preparing the super absorbent polymer according to polymerization time.
[0018] According to another embodiment of the present invention, there is provided a method for preparing a monomer composition for preparing a superabsorbent polymer, comprising the following steps: mixing an acrylic monomer having an acidic group at least a portion of which is neutralized, a cross-linking agent, a carbonate foaming agent, and a polymerization initiator, and adding clay to the mixture and shear mixing at a stirring speed of more than 6500 rpm.
[0019] According to another embodiment of the present invention, there is provided a polymer prepared from the monomer composition for preparing a super absorbent polymer, wherein, when the water content is 40 wt % to 80 wt %, the gel strength is 40000 Pa to 60000 Pa.
[0020] According to another embodiment of the present invention, there is provided a super absorbent polymer prepared from the monomer composition for preparing a super absorbent polymer, wherein the performance index (PI) represented by the following mathematical formula 1 is 2.35 or more, and T20 is less than 190 seconds:
[0021] [Calculation formula 1]
[0022] Performance index (PI) = (CRC / 27) + (AUP / 24) + (SFC / 30) - (T20 / 140)
[0023] In formula 1,
[0024] CRC is the centrifugal retention capacity (g / g) of a superabsorbent polymer for a 0.9 wt % sodium chloride aqueous solution for 30 minutes.
[0025] AUP is the absorption rate (g / g) of a superabsorbent polymer for a 0.9 wt% sodium chloride aqueous solution under a pressure of 0.7 psi for 1 hour.
[0026] SFC is the saline flow conductivity of a 0.685 wt % aqueous sodium chloride solution, and
[0027] T20 is the absorption of 20g of C by 1g of superabsorbent polymer at 0.3psi 12-14 Time (seconds) for aqueous solutions of alcohol ethoxylates.
[0028] According to another embodiment of the present invention, there is provided a method for preparing a super absorbent polymer, comprising the steps of: irradiating a monomer composition for preparing a super absorbent polymer with heat and / or light for polymerization, thereby preparing a hydrogel polymer; drying, grinding and classifying the hydrogel polymer to form a base resin; and forming a surface crosslinked layer on a surface of the base resin in the presence of a surface crosslinking solution comprising a surface crosslinking agent and a solvent.
[0029] [Beneficial Effects]
[0030] The monomer composition for preparing super absorbent polymer of the present invention has a high gelation rate after polymerization initiation and has an excellent bubble stabilization effect, so the loss of bubbles generated by the foaming agent can be minimized. Therefore, the super absorbent polymer prepared from the monomer composition for preparing super absorbent polymer of the present invention has a plurality of pores inside and can show an excellent absorption rate.
[0031] Furthermore, since the superabsorbent polymer prepared from the monomer composition for preparing the superabsorbent polymer of the present invention has high gel strength, it can well maintain its shape even after absorbing moisture, and can exhibit excellent absorption performance even under external pressure. DETAILED DESCRIPTION
[0032] The terms used herein are only used to explain the illustrative embodiments and are not intended to limit the present invention. Unless explicitly stated in the context or it is obvious that this is not intended, singular expressions include their plural expressions. As used herein, the terms "including", "equipped with" or "having" are intended to specify the presence of implemented features, quantities, steps, constituent elements or combinations thereof, and they are not intended to exclude the possibility of the presence or addition of more than one other features, quantities, steps, constituent elements or combinations thereof.
[0033] Various modifications can be made to the present invention, and the present invention can have various forms, and specific examples will be explained and explained in detail below. However, it should be understood that these are not intended to limit the present invention to specific disclosures, and the present invention includes all modifications, equivalents or substitutes thereof without departing from the spirit and technical scope of the present invention.
[0034] As used herein, "clay" refers to particles of a layered silicate mineral, or an aggregate of a plurality of such particles, and "clay dispersion" refers to a dispersion in which clay is dispersed in a solvent.
[0035] As used herein, (meth)acrylate is used to refer to acrylate and methacrylate.
[0036] As used herein, "base resin" or "base resin powder" refers to a polymer that is polymerized from a water-soluble ethylenically unsaturated monomer, dried, and ground into particles or powder, wherein surface modification or surface crosslinking is not performed.
[0037] Hereinafter, the present invention will be described in detail.
[0038] The monomer composition for preparing a superabsorbent polymer according to one embodiment of the present invention comprises: an acrylic monomer having an acidic group at least a portion of which is neutralized, a crosslinking agent, clay, a carbonate foaming agent, and a polymerization initiator.
[0039] Wherein, when the monomer composition for preparing a super absorbent polymer is irradiated with heat and / or light to perform a polymerization reaction, the normalized gel point represented by Formula 1 satisfies 0.01 to 0.1:
[0040] [Formula 1]
[0041] Normalized gel point = gel point (seconds) / total polymerization time (seconds)
[0042] In Formula 1, the gel point is the polymerization time at the intersection of a storage modulus graph of the monomer composition for preparing a super absorbent polymer according to polymerization time and a loss modulus graph of the monomer composition for preparing a super absorbent polymer according to polymerization time.
[0043] According to one embodiment, the normalized gel point of the monomer composition for preparing superabsorbent polymer may be 0.1 or less, or 0.09 or less, or 0.08 or less, or 0.06 or less, and 0.01 or more, or 0.02 or more. The method for measuring the gel point will be described in detail below.
[0044] If a polymer is formed from a monomer composition for preparing a superabsorbent polymer, the liquid monomer composition is converted into a hydrogel polymer. Therefore, the polymerization rate can be estimated by confirming the gel point (i.e., the time when the monomer composition gels). Among them, the "normalized gel point" excludes factors that the polymerization time is affected by the amount of monomer, the amount of initiator, the initial polymerization temperature and / or other polymerization conditions. By comparing the "normalized gel point", the polymerization rate of the monomer composition for preparing a superabsorbent polymer can be evaluated.
[0045] The monomer composition for preparing superabsorbent polymer of the present invention achieves faster polymerization than existing monomer compositions, thereby minimizing the loss of bubbles generated by the foaming agent, thereby improving the absorption speed of the prepared superabsorbent polymer even without excessive use of the foaming agent.
[0046] However, if the normalized gel point is less than 0.01 and the polymerization speed is too fast, gelation may proceed before the monomer composition is introduced into the polymerization reactor, and a problem of clogging of the input pipe may occur. Also, the viscosity of the monomer composition increases rapidly until the gel point, and if the gel point is less than 0.01, it is difficult to mix the monomer composition, and thus it may be difficult to form a uniform polymer. Also, if the normalized gel point is greater than 0.1, the above-mentioned bubble loss reduction effect may not be ensured, and therefore, the effect of improving the absorption speed of the superabsorbent polymer may not be expected.
[0047] Furthermore, when irradiated with heat and / or light to carry out a polymerization reaction, the monomer composition for preparing a super absorbent polymer of one embodiment can exhibit an increase rate of gel strength (storage modulus) from the gel point to the completion of polymerization (ΔG' / s, ΔG' represents the difference between the storage modulus at the completion of polymerization and the storage modulus at the gel point, and s represents the increase rate from the gel point to the completion of polymerization) of 210 Pa / s or more.
[0048] Preferably, the rate of increase of gel strength may be 215 Pa / s or more, or 220 Pa / s or more, or 230 Pa / s or more. Meanwhile, the upper limit of the rate of increase of gel strength is not specifically limited, but for example, the upper limit may be 400 Pa / s or less, or 370 Pa / s or less, or 350 Pa / s or less. Therefore, the monomer composition for preparing superabsorbent polymer of the present invention exhibits a fast polymerization rate and a high rate of increase of gel strength, and thus a polymer having excellent gel strength can be prepared.
[0049] Therefore, since the gel strength increasing speed and the gel point are improved, when the water content is 40 to 80 wt % or 40 to 60 wt %, the gel strength of the hydrogel polymer prepared from the monomer composition for preparing the superabsorbent polymer obtained after the polymerization is completed may be 35000 Pa or more, or 36000 Pa or more, or 37000 Pa or more. Meanwhile, the upper limit of the gel strength of the hydrogel polymer is not particularly limited, but, for example, the upper limit may satisfy 60000 Pa or less, or 58000 Pa or less, or 55000 Pa or less.
[0050] The monomer composition for preparing superabsorbent polymer comprises acrylic monomer, alkali metal salt or basic compound capable of neutralizing water-soluble ethylenically unsaturated monomer, crosslinking agent, clay, carbonate foaming agent and polymerization initiator, thus satisfying the above-mentioned properties. Specifically, the monomer composition for preparing superabsorbent polymer of the present invention comprises clay as an additive, and since the clay is uniformly dispersed in the monomer composition, the above-mentioned properties can be exhibited.
[0051] The acrylic monomer is a compound represented by the following Chemical Formula 1:
[0052] [Chemical formula 1]
[0053] R 1 -COOM 1
[0054] R is a C2-5 alkyl group containing an unsaturated bond,
[0055] M 1 It is a hydrogen atom, a monovalent or divalent metal, an ammonium group or an organic amine salt.
[0056] Preferably, the monomer includes at least one selected from the group consisting of acrylic acid, methacrylic acid, and monovalent metal salts, divalent metal salts, ammonium salts, and organic amine salts thereof.
[0057] Wherein, acrylic monomer has acidic group, and at least part of acidic group can be neutralized.Preferably, monomer can be partially neutralized with alkaline substances such as sodium hydroxide, potassium hydroxide, ammonium hydroxide before use.Wherein, the neutralization degree of the acrylic monomer is 40 mol % to 95 mol % or 40 mol % to 80 mol % or 45 mol % to 75 mol %.The scope of neutralization degree can be controlled according to final property.But, if the neutralization degree is too high, the neutralized monomer may be extracted, on the contrary, if the neutralization degree is too low, the absorption power of the polymer may be significantly reduced, and the polymer may show the property of difficult-to-handle similar elastic rubber.
[0058] The concentration of the acrylic monomer may be about 20 wt % to about 60 wt %, preferably about 40 wt % to about 50 wt %, based on the monomer composition including the raw material of the super absorbent polymer and the solvent, and the concentration of the acrylic monomer may be appropriately controlled in consideration of the polymerization time and reaction conditions, etc. However, if the concentration of the monomer is too low, the yield of the super absorbent polymer may be low, thereby causing problems in economic feasibility, whereas if the concentration is too high, a portion of the monomer may be extracted, or the grinding efficiency of the hydrogel polymer may be low, thereby causing processing problems, and the properties of the super absorbent polymer may be deteriorated.
[0059] As the crosslinking agent, any compound can be used as long as they can introduce crosslinking during the polymerization of the acrylic monomer. The crosslinking agent is also expressed as an "internal crosslinking agent" in order to distinguish it from a "surface crosslinking agent" used for surface crosslinking of superabsorbent polymer particles. Although the crosslinking is performed without distinguishing between the surface or the inside due to the crosslinking agent contained in the monomer composition, in the case of performing a surface crosslinking process on the superabsorbent polymer particles obtained after polymerizing, drying, grinding and classifying the monomer composition, the particle surface of the superabsorbent polymer finally prepared may consist of a structure crosslinked by the surface crosslinking agent, and the inside may consist of a structure crosslinked by the internal crosslinking agent.
[0060] Specifically, as the cross-linking agent contained in the monomer composition, a cross-linking agent having one or more functional groups capable of reacting with the water-soluble substituent of the acrylic monomer and at the same time having one or more ethylenically unsaturated groups can be used; or a cross-linking agent having two or more functional groups capable of reacting with the water-soluble substituent of the monomer and / or the water-soluble substituent formed by hydrolysis of the monomer can be used.
[0061] As a non-limiting example, as the crosslinking agent, the following multifunctional crosslinking agents can be used alone or in combination of two or more thereof, but are not limited thereto, for example: N,N'-methylenebisacrylamide, trimethylpropane tri(meth)acrylate, ethylene glycol di(meth)acrylate, polyethylene glycol (meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, polypropylene glycol (meth)acrylate, butanediol di(meth)acrylate, butanediol di(meth)acrylate, diethylene glycol di(meth)acrylate, hexanediol di(meth)acrylate, triethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, dipentaerythritol pentaacrylate, glycerol tri(meth)acrylate, pentaerythritol tetraacrylate, triarylamine, ethylene glycol diglycidyl ether, propylene glycol, glycerol or ethylene carbonate.
[0062] Preferably, as the crosslinking agent, a polyalkylene glycol di(meth)acrylate compound can be used, such as polyethylene glycol (meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate or polypropylene glycol (meth)acrylate. When such a crosslinking agent is used, foaming by a carbonate foaming agent described below can be easily performed.
[0063] In the monomer composition, such a crosslinking agent may be used in an amount of 0.01 to 5 parts by weight based on 100 parts by weight of the acrylic monomer. For example, the crosslinking agent may be used in an amount of 0.01 or more parts by weight, 0.05 or more parts by weight, 0.1 or more parts by weight, and less than 5 parts by weight, less than 3 parts by weight, less than 2 parts by weight, less than 1 part by weight, or less than 0.7 parts by weight based on 100 parts by weight of the acrylic monomer. If the content of the crosslinking agent is too low, crosslinking may not occur sufficiently, and therefore it may be difficult to achieve a strength higher than an appropriate level, and if the content of the crosslinking agent is too high, the internal crosslinking density may increase, and therefore it may be difficult to achieve the desired centrifugal retention capacity.
[0064] In addition, the monomer composition contains a polymerization initiator for initiating a polymerization reaction of the monomers. The polymerization initiator is not particularly limited as long as it is generally used in the preparation of super absorbent polymers.
[0065] Specifically, as the polymerization initiator, a thermal polymerization initiator, a redox pair initiator, or a photopolymerization initiator according to ultraviolet irradiation may be used according to the polymerization method. However, even in the case of photopolymerization, a certain amount of heat is generated due to ultraviolet irradiation, etc., and heat is generated to a certain extent according to the progress of the exothermic polymerization reaction, so a thermal polymerization initiator may be additionally contained.
[0066] The photopolymerization initiator may be used without limitation in structure as long as it is a compound capable of forming radicals by light (eg, ultraviolet rays).
[0067] As the photopolymerization initiator, one or more compounds selected from the group consisting of benzoin ether, dialkyl acetophenone, hydroxyalkyl ketone, phenyl glyoxylate, benzyl dimethyl ketal, acyl phosphine and α-amino ketone can be used. Among them, as a specific example of acyl phosphine, lucirin TPO, i.e. 2,4,6-trimethylbenzoyl trimethyl phosphine oxide, can be used. More photoinitiators are described on page 115 of "UV Coatings: Basics, Recent Developments and New Application (Elsevier 2007)" by Reinhold Schwalm, and are not limited to the above examples.
[0068] The concentration of the photopolymerization initiator may be about 0.001 wt % to about 1.0 wt % based on the monomer composition. If the concentration of the photopolymerization initiator is too low, the polymerization speed may be slow, and if the concentration of the photopolymerization initiator is too high, the molecular weight of the superabsorbent polymer may be low and the properties may become uneven.
[0069] As the thermal polymerization initiator, one or more selected from persulfate initiators, azo initiators, hydrogen peroxide and ascorbic acid can be used. Specifically, as examples of persulfate initiators, sodium persulfate (Na2S2O8), potassium persulfate (K2S2O8), ammonium persulfate ((NH4)2S2O8) and the like can be mentioned, and as examples of azo initiators, 2,2-azobis(2-amidinopropane) dihydrochloride, 2,2-azobis-(N,N-dimethylene)isobutylamidine dihydrochloride, 2-(carbamoyl azo)isobutyronitrile, 2,2-azobis[2-(2-imidazoline-2-yl)propane] dihydrochloride, 4,4-azobis-(4-cyanovaleric acid) and the like can be mentioned. More thermal polymerization initiators are described on page 203 of Odian's "Principle of polymerization (Wiley, 1981)", but the present invention is not limited thereto.
[0070] The content of the thermal polymerization initiator may be about 0.001 wt % to about 0.5 wt % based on the monomer composition. If the concentration of the thermal polymerization initiator is too low, additional thermal polymerization may be difficult to occur, and thus, the effect of adding the thermal polymerization initiator may not be significant, and if the concentration of the thermal polymerization initiator is too high, the molecular weight of the superabsorbent polymer may become small and the properties may become uneven.
[0071] The redox pair initiator is a material that causes a redox reaction with each other in the monomer composition, for example, potassium metabisulfite and sodium persulfate; or ascorbic acid and hydrogen peroxide can be used as the redox pair initiator.
[0072] The redox pair initiator initiates polymerization prior to photopolymerization due to free radicals generated during the redox process and is therefore preferably introduced into the monomer composition prior to polymerization. The redox pair initiator (i.e., each oxidizing agent and reducing agent) may be used in an amount of about 0.001 wt % to about 0.5 wt % based on the monomer composition.
[0073] Clay is included in the monomer composition to improve polymerization rate and increase gel strength. As used herein, "clay" refers to nanometer-sized clay particles, or agglomerates of a plurality of such particles.
[0074] As the clay, expandable or non-expandable clay can be used. Expandable clay is a layered organic matter having water absorption power, and montmorillonite, saponite, nontronite, laponite, beidellite, hectorite, vermiculite, magadiite, bentonite, etc. can be used, and as non-expandable clay, kaolin, serpentine, mica, etc. can be used. One kind of clay can be used alone, or two or more kinds of clays can be used in combination.
[0075] As the clay, a clay having an average particle size (D50) of 0.025 μm or more, 0.05 μm or more, 0.1 μm or more, or 1 μm or more, and 10 μm or less, 8 μm or less, 5 μm or less, or 3 μm or less can be used. If the average particle size (D50) of the clay is less than 0.025 μm, the effect of improving the gel strength of the superabsorbent polymer may not be fully obtained. If the average particle size (D50) of the clay is greater than 10 μm, it may be difficult to form a uniform aqueous dispersion due to the strong interlayer attraction of the clay, and thus the transmittance may not be ensured after dispersion.
[0076] Here, "particle size Dn" refers to the particle size at the n% point of the cumulative distribution of the number of particles according to the particle size, and D50 refers to the particle size at the 50% point of the cumulative distribution of the number of particles according to the particle size. The average particle size (D50) of the clay can be measured by laser diffraction and dynamic light scattering using a particle size analyzer. Specifically, the powder to be tested is dispersed in a dispersion medium and introduced into a commercially available laser diffraction particle size measuring device (e.g., Mastersizer 3000 from Malvern) to measure the difference in the diffraction pattern according to the particle size when the particles pass through the laser beam, thereby generating a particle size distribution. D50 can be measured by calculating the particle diameter at the 50% point of the cumulative distribution of the particle count according to the particle diameter in the arrival measuring device.
[0077] Based on 100 parts by weight of the acrylic monomer, the content of the clay may be 0.1 parts by weight or more, or 0.2 parts by weight or more, or 0.25 parts by weight or more, and 10 parts by weight or less, or 7 parts by weight or less, or 5 parts by weight or less, or 3 parts by weight or less, or 1 part by weight or less. If the content of the clay is less than 0.1 parts by weight based on 100 parts by weight of the acrylic monomer, the above-mentioned normalized gel point range may not be satisfied. And, if the content of the clay is greater than 10 parts by weight based on 100 parts by weight of the acrylic monomer, it may be difficult to evenly disperse in the monomer composition, and the effect of improving the absorption rate of the obtained superabsorbent polymer may not be obtained.
[0078] Meanwhile, in order to satisfy the above-mentioned gel point property, the clay needs to be uniformly dispersed in the monomer composition.
[0079] In this regard, it is preferred to use a clay which has been delaminated by physical or chemical means, or to cause the clay to be delaminated within the monomer composition.
[0080] Clay has a layered structure in which small silicate plates with a thickness of about 1 nm are stacked one on top of the other due to strong van der Waals attraction, and the distance between each layer is about 1 nm. Delaminated clay is clay in which the silicate layers have been delaminated (i.e. spread out) by physical or chemical means so that the distance between the layers exceeds 1 nm. Delaminated clay behaves as a more stable dispersion in the composition.
[0081] For example, clay surface-modified with a polymer dispersant containing two or more functional groups selected from the group consisting of an amine group, a carbonyl group, and a hydroxyl group can be used as the clay. Such clay has significantly improved dispersion stability when the layered structure is delaminated by the polymer dispersant, and therefore, even if contained in a composition for preparing a superabsorbent polymer containing an alkali metal salt or a basic compound, the clay particles can be uniformly dispersed in the composition without agglomeration or sedimentation.
[0082] Throughout the specification, “two or more functional groups selected from the group consisting of an amine group, a carbonyl group, and a hydroxyl group” is used to include functional groups composed of two or more combinations of amine groups, carbonyl groups, and hydroxyl groups, such as an amide group containing both an amine group and a carbonyl group, a carboxyl group containing both a carbonyl group and a hydroxyl group, etc. For example, a “polymer dispersant containing an amine group and a carbonyl group” may contain an amine group and a carbonyl group, respectively, in the molecule, or may contain an amide group composed of a combination of an amine group and a carbonyl group.
[0083] The polymer dispersant containing this functional group can be bonded to the surface of the clay due to the unshared electrons of the nitrogen and oxygen atoms, and in the composition for preparing the superabsorbent polymer at a high ion concentration, a charge can be induced in the polymer due to resonance. Due to these properties, the polymer dispersant can improve the dispersibility of the clay by delaminating the layered structure of the clay. In addition, the polymer dispersant does not cause discoloration of the superabsorbent polymer or deteriorate the properties, and therefore, it can be appropriately used to prepare the superabsorbent polymer.
[0084] In this regard, preferably, the polymer dispersant comprises an amine group and a carbonyl group; or a carbonyl group and a hydroxyl group. More preferably, the polymer dispersant may comprise an amide group and / or a carboxyl group.
[0085] As specific examples of the polymer dispersant, one or more selected from the group consisting of polyvinyl pyrrolidone, polyacrylamide, and polyacrylic acid may be mentioned. Preferably, polyvinyl pyrrolidone may be used as the polymer dispersant.
[0086] Although the molecular weight of the polymer dispersant is not particularly limited, for example, a polymer dispersant having a weight average molecular weight of 2500 g / mol or more, or 5000 g / mol or more, or 10000 g / mol or more, and 200000 g / mol or less, or 100000 g / mol or less, or 40000 g / mol may be used. If the weight average molecular weight of the polymer dispersant is less than 2500 g / mol, when the polymer dispersant is bonded to the clay surface, it may be difficult to sufficiently ensure the distance between the silicate layers of the clay, and therefore, there may be problems in terms of dispersibility and long-term stability, and if it is greater than 200000 g / mol, there may be process difficulties, and the surface modification of the clay may not be effectively performed, and therefore it is preferred to satisfy the above range.
[0087] The weight average molecular weight of the polymeric dispersant can be determined by gel permeation chromatography (GPC) using polystyrene standards.
[0088] For example, GPC analysis can be performed using a Polymer Laboratories PLgelMIX-B 300 mm long column in a Waters PL-GPC220 instrument under the following conditions.
[0089] Column temperature: 160°C
[0090] Solvent: 1,2,4-Trichlorobenzene
[0091] Flow rate: 1mL / min
[0092] Sample: Mix to a concentration of 10 mg / 10 mL and then supply a volume of 200 μL.
[0093] The mW and Mn values were obtained using a calibration curve formed from polystyrene standards (9 types of polystyrene standards with molecular weights of 2000 / 10000 / 30000 / 70000 / 200000 / 700000 / 2000000 / 4000000 / 10000000).
[0094] The polymer dispersant may be used in an amount of greater than 20 to less than 200 parts by weight, preferably greater than 23 parts by weight or greater than 25 parts by weight, and less than 150 parts by weight or less than 100 parts by weight, based on 100 parts by weight of the clay, to ensure dispersibility of the clay.
[0095] If the content of the polymer dispersant is less than 20 parts by weight based on 100 parts by weight of the clay, the degree of surface modification of the clay may be insufficient, and thus the interlayer distance between the clays may not be sufficiently widened. Therefore, the dispersion stability of the clay may be insufficient, and thus the clay particles may easily agglomerate. Also, if the content of the polymer dispersant is greater than 200 parts by weight based on 100 parts by weight of the clay, the polymer dispersant may reduce the property improvement effect that the clay can provide, and thus the properties of the superabsorbent polymer may be deteriorated.
[0096] The clay surface modified with a polymer dispersant can be prepared by adding clay and a polymer dispersant to a solvent such as water, a lower alcohol (e.g., ethanol, ethylene glycol), and stirring. Also, the clay surface modified with a polymer dispersant can be added to the monomer composition for preparing a superabsorbent polymer in the form of a dispersion dispersed in a solvent. As a solvent for preparing the clay dispersion, a solvent used for preparing the monomer for superabsorbent polymer can be used, and the amount of the solvent used can be appropriately controlled in consideration of the type and amount of the clay and the polymer dispersant, and the purpose of the clay dispersion, etc.
[0097] For example, the dispersion containing the polymer dispersant surface-modified clay may contain clay in an amount of 1 part by weight or more, or 3 parts by weight or more, and 20 parts by weight or less, or 10 parts by weight or less, or 8 parts by weight or less in 100 parts by weight of the dispersion.
[0098] Meanwhile, in the case of using non-surface modified clay, the clay dispersion can be shear mixed and added to the monomer composition, or alternatively, the clay can be added to the monomer composition and then shear mixed. Such shear mixing can physically delaminate the clay, thereby allowing the clay to be more evenly and stably dispersed in the monomer composition.
[0099] With regard to the solvent and clay content in the dispersion used to prepare the clay dispersion containing non-surface-modified clay, reference may be made to the description of the dispersion containing the polymer dispersant surface-modified clay.
[0100] Shear mixing can be performed using devices such as an in-line high shear mixer, a high shear batch mixer, or a homogenizer.
[0101] Shear mixing can be performed at a stirring speed of 6500 rpm or more, or 9000 rpm or more, or 12000 rpm or more. Although the upper limit of the stirring speed is not specifically limited, for example, the upper limit may be 50000 rpm or less, or 40000 rpm or less, or 30000 rpm or less.
[0102] The clay can be physically separated by shear mixing at such a stirring speed for at least 10 seconds, preferably 20 seconds or more, or 30 seconds or more. If the shear mixing time is too long, heat may be generated due to the shear force, so it is preferred that the shear mixing is performed for 3 minutes or less, or 1 minute or less.
[0103] Meanwhile, in the case where clay is introduced into the monomer composition and then shear mixed, in order to achieve a more uniform degree of dispersion, non-surface modified clay can be added to the monomer composition in the form of an aqueous dispersion. The clay aqueous dispersion can be prepared by mixing water and clay using the above-mentioned shear mixing device at a stirring speed of more than 6500rpm, or more than 9000rpm, or more than 12000rpm. Although there is no specific limit to the upper limit of the stirring speed during shear mixing, for example, the upper limit can be less than 50000rpm, or less than 40000rpm, or less than 30000rpm. By mixing at the above-mentioned stirring speed for more than 10 seconds, or more than 20 seconds, or more than 30 seconds, and less than 5 minutes, or less than 3 minutes, an aqueous dispersion of clay can be prepared.
[0104] Among them, the concentration of the clay aqueous dispersion (i.e., the content of clay in 100 parts by weight of the clay aqueous dispersion) is 0.5 parts by weight or more, or 1.0 parts by weight or more, or 2.0 parts by weight or more, and is 5.0 parts by weight or less, or 4.0 parts by weight or less, which can be suitable for ensuring uniform dispersibility.
[0105] As described above, by surface-modifying the clay using a polymer dispersant, or by physically demixing the non-surface-modified clay, the clay can be uniformly dispersed in the monomer composition, and the prepared monomer composition can satisfy the above-mentioned gel point properties.
[0106] Meanwhile, whether the clay is "uniformly dispersed" in the monomer composition can be judged by whether the monomer composition is demixed when the clay is mixed and then left to stand for 1 minute. That is, in the case where demixing does not occur even after the monomer composition is left to stand for 1 minute, it can be predicted that the clay is uniformly dispersed in the monomer composition, and therefore, the composition can satisfy the above-mentioned gel point property.
[0107] The carbonate foaming agent foams during the polymerization process, thereby playing a role in forming pores in the hydrogel polymer to increase the surface area, and for example, one or more selected from the group consisting of sodium bicarbonate, sodium carbonate, potassium bicarbonate, potassium carbonate, calcium bicarbonate, calcium bicarbonate, magnesium bicarbonate and magnesium carbonate can be used.
[0108] Based on 100 parts by weight of acrylic monomers, the amount of carbonate foaming agent can be 0.005 parts by weight to 1 part by weight. If the content of the foaming agent is less than 0.005 parts by weight, the function as a foaming agent may not be significant. If the content of the foaming agent is greater than 1 part by weight, the gel strength of the prepared superabsorbent polymer may be reduced due to excessive pores in the cross-linked polymer, and the density may be reduced, thus causing problems in circulation and storage. For example, based on 100 parts by weight of acrylic monomers, the amount of carbonate foaming agent can be 0.01 parts by weight or more, 0.05 parts by weight or more, and 0.5 parts by weight or less, 0.3 parts by weight or less, or 0.2 parts by weight or less.
[0109] When preparing the monomer composition, surfactants commonly used as bubble stabilizers, such as alkyl sulfate compounds and polyoxyethylene alkyl ether compounds, may not be used. For example, in step 1 and step 2, cationic surfactants such as quaternary ammonium compounds, such as dodecyltrimethylammonium chloride, dodecyltrimethylammonium bromide, etc.; anionic surfactants such as alkyl sulfate compounds, such as sodium lauryl sulfate, ammonium lauryl sulfate, sodium lauryl ether sulfate, or sodium myristyl alcohol polyether sulfate, etc.; or nonionic surfactants such as alkyl ether sulfate compounds, such as polyoxyethylene lauryl ether, etc., may not be used. Thus, the reduction in the surface tension of the superabsorbent polymer due to the use of a surfactant can be prevented.
[0110] The monomer composition may further contain additives such as a thickener, a plasticizer, a preservative, an antioxidant, and the like as required.
[0111] Furthermore, the monomer composition containing the monomer may be in a solution state dissolved in a solvent such as water, and the solid content in the monomer composition in the solution state, i.e., the concentrations of the monomer, the crosslinking agent, and the polymerization initiator may be appropriately controlled in consideration of the polymerization time and the reaction conditions, etc. For example, the solid content in the monomer composition may be 10 to 80% by weight, or 15 to 60% by weight, or 30 to 50% by weight.
[0112] When the monomer composition has the above solid content range, due to the gelation effect occurring in the polymerization reaction of the high concentration aqueous solution, it is not necessary to remove the unreacted monomer after the polymerization, and it is also beneficial to control the grinding efficiency during the grinding process of the polymer as described below.
[0113] Among them, the solvent that can be used is not limited as long as it can dissolve the above-mentioned raw materials. For example, water, ethanol, ethylene glycol, diethylene glycol, triethylene glycol, 1,4-butanediol, propylene glycol, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, methyl ethyl ketone, acetone, methyl amyl ketone, cyclohexanone, cyclopentanone, diethylene glycol monomethyl ether, diethylene glycol ethyl ether, toluene, xylene, butyrolactone, carbitol, methyl cellosolve acetate and N,N-dimethylacetamide or a mixture thereof can be used.
[0114] Meanwhile, according to one embodiment of the present invention, there is provided a method for preparing a super absorbent polymer, which comprises the following steps: irradiating a monomer composition for preparing a super absorbent polymer with heat and / or light for polymerization, thereby preparing a hydrogel polymer; drying, grinding and classifying the hydrogel polymer to form a base resin; and forming a surface crosslinked layer on the surface of the base resin in the presence of a surface crosslinking solution comprising a surface crosslinking agent and a solvent.
[0115] The method of polymerizing the monomer composition for preparing the superabsorbent polymer is not specifically limited. According to the polymerization energy source, the polymerization method is mainly divided into thermal polymerization and photopolymerization. Generally, thermal polymerization can be carried out in a reactor equipped with a stirring shaft (such as a kneader), and photopolymerization can be carried out in a reactor equipped with a movable conveyor belt or in a flat-bottomed container, but the above-mentioned polymerization method is only an example, and the present invention is not limited thereto.
[0116] For example, the hydrogel polymer can be obtained by introducing the monomer composition into a reactor equipped with a stirring shaft (such as the above-mentioned kneading machine), and supplying hot air or heating the reactor to perform thermal polymerization. Wherein, according to the shape of the stirring shaft equipped in the reactor, the size of the hydrogel polymer discharged to the reactor outlet can be several centimeters to several millimeters. Specifically, the size of the obtained hydrogel polymer can vary according to the concentration and introduction speed of the introduced monomer composition, and generally, a hydrogel polymer with a particle size of 2 mm to 50 mm can be obtained.
[0117] And, in the case where the photopolymerization of the monomer composition is carried out in the above-mentioned reactor equipped with a movable conveyor belt, the obtained hydrogel polymer can generally be a hydrogel polymer sheet having a width of the conveyor belt. Wherein, the thickness of the sheet may vary depending on the concentration and introduction speed of the introduced monomer composition, but preferably, the monomer composition is supplied to obtain a polymer sheet having a thickness of about 0.5 cm to about 5 cm. In the case where the thickness of the polymer sheet may become too thin due to the feeding of the monomer composition, the production efficiency may be low, and if the thickness of the polymer sheet is greater than 5 cm, polymerization may not occur uniformly over the entire thickness due to the excessive thickness.
[0118] The water content of the hydrogel polymer thus obtained is generally 40% to 80% by weight. Throughout the specification, "water content" is the content of water based on the total weight of the hydrogel polymer, and refers to a value obtained by subtracting the weight of the polymer in a dry state from the weight of the hydrogel polymer. Specifically, the water content is defined as a value calculated by measuring the weight loss according to the evaporation of water in the polymer while increasing the temperature of the polymer by infrared heating for drying. Wherein the temperature is increased from room temperature to about 180°C and then maintained at 180°C, and the total drying time is 20 minutes, including a 5-minute temperature increase step.
[0119] Next, a step of drying and classifying the hydrogel polymer to form a base resin in a powder form is performed. In order to improve the efficiency of the drying step, a coarse grinding step may be further performed before drying as needed.
[0120] Among them, the usable grinding machine is not limited in structure, but specifically, one selected from the group consisting of a vertical crusher, a turbine cutter, a turbine grinder, a rotary cutting mill, a cutting mill, a disc mill, a pulverizing crusher, a crusher, a shredder, and a disc cutter can be used, but the present invention is not limited thereto.
[0121] Among them, grinding can be performed so that the particle size of the polymer can become about 2 mm to 10 mm. Due to the high water content of the hydrogel polymer, grinding to a particle size of less than 2 mm will not be technically easy and may cause agglomeration between the ground particles. At the same time, if grinding to a particle size greater than 10 mm, the effect of improving the efficiency of the subsequent drying step may not be significant.
[0122] The polymer ground as described above is dried, or the polymer is dried immediately after polymerization without a grinding step. The drying temperature of the drying step may be about 150°C to about 250°C. If the drying temperature is less than 150°C, the drying time may be excessively extended, and the properties of the superabsorbent polymer finally prepared may be deteriorated. If the drying temperature is greater than 250°C, only the surface of the polymer may be dried, so fine particles may be produced in the subsequent grinding process, and the properties of the superabsorbent polymer finally prepared may be deteriorated. Therefore, the drying may preferably be carried out at a temperature of about 150°C to about 200°C, more preferably at a temperature of about 160°C to about 180°C.
[0123] Meanwhile, considering process efficiency, the drying may be performed for about 20 minutes to about 90 minutes, but the drying time is not limited thereto.
[0124] And, the drying method is not limited as long as it is generally used as a drying process for hydrogel polymers. Specifically, the drying can be performed by hot air supply, infrared irradiation, microwave irradiation, or ultraviolet irradiation, etc. The water content of the polymer after the drying step can be about 0.1 wt% to about 5 wt%.
[0125] Next, a step of grinding the dried polymer obtained in the drying step is performed.
[0126] The particle size of the polymer powder (i.e., base resin) obtained after the grinding step may be about 150 μm to about 850 μm. As a grinder for grinding to such a particle size, specifically, a ball mill, a pin mill, a hammer mill, a screw mill, a roller mill, a disc mill or a slow mill, etc. may be used, but the present invention is not limited thereto.
[0127] And, in order to manage the performance of the superabsorbent polymer powder of the final product after the grinding step, the base resin obtained after grinding is classified according to the particle size. Preferably, the polymer with a particle size of about 150 μm to about 850 μm is classified, and only the base resin with such a particle size can be subjected to the surface crosslinking reaction step. Such particle diameter can be measured according to the European Disposables and Nonwovens Association (EDANA) standard EDANAWSP 220.3 method.
[0128] Next, a step of additionally crosslinking the surface of the base resin in the presence of a surface crosslinking agent to form a surface crosslinked layer is performed. Through this step, a superabsorbent polymer forming a surface crosslinked layer on the surface of the base resin, more specifically, a superabsorbent polymer forming a surface crosslinked layer on at least a portion of each surface of the base resin particles is provided.
[0129] Surface crosslinking is a step of increasing the crosslinking density around the surface of a superabsorbent polymer particle relative to the crosslinking density inside the particle. Typically, a surface crosslinking agent is applied to the surface of the superabsorbent polymer particle. Thus, the reaction occurs on the surface of the superabsorbent polymer particle, which improves the crosslinking of the particle surface without substantially affecting the interior of the particle. Thus, surface crosslinked superabsorbent polymer particles have a higher crosslinking density around the surface than inside.
[0130] As a surface crosslinking agent, a crosslinking agent previously used for preparing superabsorbent polymers can be used without specific restrictions. For example, the surface crosslinking agent may include one or more polyols selected from the group consisting of ethylene glycol, propylene glycol, 1,3-propylene glycol, 1,4-butylene glycol, 1,6-hexanediol, 1,2-hexanediol, 1,3-hexanediol, 2-methyl-1,3-propylene glycol, 2,5-hexanediol, 2-methyl-1,3-pentanediol, 2-methyl-2,4-pentanediol, tripropylene glycol and glycerol; one or more carbonate compounds selected from the group consisting of ethylene carbonate, propylene carbonate and glycerol carbonate; epoxy compounds such as ethylene glycol diglycidyl ether, etc.; oxazolidinone compounds such as 2-oxazolidinone, etc.; polyamine compounds; oxazoline compounds; mono-, di- or poly-oxazolidinone compounds; or cyclic urea compounds, etc. Specifically, as a surface crosslinking agent, one or more, or two or more, or three or more of the above-mentioned surface crosslinking agents can be used. For example, ethylene carbonate can be used as the surface cross-linking agent.
[0131] The method of mixing the surface crosslinking agent with the base resin is not limited. The surface crosslinking agent and the base resin powder may be placed in a reactor and mixed, the surface crosslinking agent may be sprayed onto the base resin powder, or the base resin and the surface crosslinking agent may be continuously fed into a continuously operated mixer and mixed, etc.
[0132] When adding a surface crosslinking agent, it can be added in the form of a surface crosslinking solution by mixing water together. In the case of adding water, the surface crosslinking agent can be evenly dispersed in the polymer. Wherein, based on 100 parts by weight of the base resin, water is preferably added in a ratio of about 1 part by weight to about 10 parts by weight so that the surface crosslinking agent is evenly dispersed, preventing the polymer powder from agglomerating, and optimizing the surface penetration depth of the surface crosslinking agent.
[0133] The surface crosslinking reaction can be carried out by heating the base resin to which a surface crosslinking solution comprising a surface crosslinking agent and a solvent is added at a temperature of about 100° C. to about 150° C., preferably about 110° C. to about 140° C., for about 15 minutes to about 80 minutes, preferably about 20 minutes to about 70 minutes.
[0134] The temperature raising method of the surface cross-linking is not specifically limited, and a heat transfer medium may be supplied or a heat source may be directly supplied for heating. Among them, as an available heat transfer medium, steam, hot air, a high temperature fluid such as hot oil, etc. may be used, and the temperature of the supplied heat transfer medium may be appropriately selected in consideration of the heat transfer medium, the temperature raising method, and the target temperature. Meanwhile, as a directly supplied heat source, electric heating or gas heating may be mentioned, but the present invention is not limited thereto.
[0135] The monomer composition for preparing the superabsorbent polymer has a high gelation rate after initiating polymerization, thereby minimizing the loss of bubbles generated by the foaming agent. Therefore, the monomer composition for preparing the superabsorbent polymer can provide a superabsorbent polymer showing an excellent absorption rate.
[0136] Specifically, the super absorbent polymer prepared from the monomer composition for preparing the super absorbent polymer may satisfy the performance index (PI) represented by the following mathematical formula 1 of 2.35 or more, and T20 of less than 190 seconds:
[0137] [Calculation formula 1]
[0138] Performance index (PI) = (CRC / 27) + (AUP / 24) + (SFC / 30) - (T20 / 140)
[0139] In formula 1,
[0140] CRC is the centrifugal retention capacity (g / g) of a superabsorbent polymer for a 0.9 wt % sodium chloride aqueous solution for 30 minutes.
[0141] AUP is the pressure absorption rate (g / g) of a superabsorbent polymer for a 0.9 wt% sodium chloride aqueous solution at 0.7 psi for 1 hour.
[0142] SFC is the saline conductivity of 0.685 wt% sodium chloride aqueous solution (·10 -7 cm 3 s / g), and
[0143] T20 is the time (seconds) it takes for 1 g of superabsorbent polymer to absorb 20 g of an aqueous solution of C12-14 alcohol ethoxylate at 0.3 psi.
[0144] The measurement methods of CRC, AUP, SFC and T20 will be specifically described in the following examples.
[0145] The super absorbent polymer prepared from the monomer composition for preparing the super absorbent polymer has a form in which the above-mentioned clay is uniformly dispersed inside and outside.
[0146] Preferably, the PI of the superabsorbent polymer may be 2.37 or more, 2.40 or more, or 2.41 or more, and 4.0 or less, or 3.0 or less. Also, the T20 of the superabsorbent polymer may be 180 seconds or less, 160 seconds or less, 140 seconds or less, 130 seconds or less, or 125 seconds or less, and 100 seconds or more.
[0147] Also, the superabsorbent polymer prepared from the monomer composition for preparing the superabsorbent polymer of the present invention has high gel strength and can well maintain its shape even after absorbing moisture, and thus, the superabsorbent polymer can exhibit excellent absorption performance even under external pressure.
[0148] In the following, preferred examples are shown for a better understanding of the present invention, but these examples are shown only as illustrations of the present invention, and it is obvious to those skilled in the art that various changes and modifications can be made within the scope of the category and technical concept of the present invention, and these changes and modifications fall within the scope of the appended claims.
[0149] [Example]
[0150] Comparative Example 1
[0151] (1) Preparation of monomer composition for preparing superabsorbent polymer
[0152] In a 3 L glass container equipped with a stirrer and a thermometer, 450 g of acrylic acid, 3 g of PEGDA 400 (polyethylene glycol diacrylate 400) internal crosslinking agent, and 0.04 g of diphenyl (2,4,6-trimethylbenzoyl) -phosphine oxide photoinitiator were added and dissolved, and then 580 g of 31.5% sodium hydroxide solution was added to prepare a monomer mixture (neutralization degree: 70 mol%; solid content: 41 wt%).
[0153] To the monomer mixture, 0.1 parts by weight of sodium bicarbonate (SBC) as a carbonate-based foaming agent was added based on 100 parts by weight of acrylic acid to prepare a monomer composition for preparing a super absorbent polymer.
[0154] (2) Preparation of superabsorbent polymer
[0155] A portion (86.6 g) of the monomer composition for preparing the superabsorbent polymer prepared in (1) was placed in a rheometer (TAInstruments, ARES) equipped with an ultraviolet attachment and subjected to ultraviolet polymerization for 180 seconds by irradiating ultraviolet rays. Specifically, the polymerization temperature was maintained at 60° C., and ultraviolet rays were irradiated for 60 seconds (irradiation amount: 100 mW / cm 2 ), and the reaction was carried out for an additional 120 seconds.
[0156] The storage modulus (G') and loss modulus (G") of the monomer composition were measured from the time of polymerization initiation, and the curves were plotted against the polymerization time. The water content of the hydrogel polymer obtained after the polymerization reaction was measured and confirmed to be 48 wt%.
[0157] The remaining part of the monomer composition for preparing the superabsorbent polymer which was not added to the rheometer was introduced into a polymerization chamber whose temperature was controlled to 60°C, in which an ultraviolet light source was present in the upper part, and then ultraviolet rays were irradiated for 60 seconds, and the reaction was performed for an additional 120 seconds to obtain a hydrogel polymer. The prepared hydrogel polymer was cut into a size of about 5 cm × 5 cm, and then introduced into a meat grinder to grind the polymer, thereby obtaining hydrogel crumbs with a size of 1 mm to 10 mm. Then, the crumbs were dried in an oven capable of transferring airflow up and down. The crumbs were uniformly dried by flowing hot air above 180°C from the lower part to the upper part for 15 minutes, and then from the upper part to the lower part for 15 minutes, and dried so that the moisture content of the dried main body after drying became less than 1%. After drying, it was ground with a grinder, and classified to select those with a size of 150 μm to 850 μm, thereby preparing a base resin.
[0158] A surface crosslinking solution was sprayed onto 100 parts by weight of the above prepared base resin, the surface crosslinking solution comprising 1.5 parts by weight of ethylene carbonate and 6 parts by weight of water based on 100 parts by weight of the base resin, and stirred and mixed at room temperature so that the surface crosslinking solution was uniformly distributed on the surface of the base resin powder. Subsequently, the base resin powder mixed with the surface crosslinking solution was placed in a surface crosslinking reactor, and a surface crosslinking reaction was performed.
[0159] In the surface crosslinking reactor, it was confirmed that the temperature of the base resin powder gradually increased from the initial temperature of about 80°C, and the operation was performed so that the maximum reaction temperature of 190°C was reached after 30 minutes. After reaching the maximum reaction temperature, the reaction was performed for an additional 15 minutes, and then the finally prepared super absorbent polymer sample was taken out. After the surface crosslinking process, it was classified with an ASTM standard sieve to prepare a super absorbent polymer with a particle size of 150 μm to 850 μm.
[0160] Example 1
[0161] In a 3 L glass container equipped with a stirrer and a thermometer, 450 g of acrylic acid, 3 g of PEGDA 400 (polyethylene glycol diacrylate 400) internal crosslinking agent, and 0.04 g of diphenyl (2,4,6-trimethylbenzoyl) -phosphine oxide photoinitiator were added and dissolved, and then 580 g of 31.5% sodium hydroxide solution was added to prepare a monomer mixture (neutralization degree: 70 mol%; solid content: 41 wt%).
[0162] To the monomer mixture, an aqueous dispersion of kaolin (average particle size (D50) of 0.6 μm) was added so that the kaolin content based on 100 parts by weight of acrylic acid became 0.25 parts by weight, and dispersed by mixing at 6500 rpm for 3 minutes using a homogenizer (IKA, Ultra-turrax). The aqueous dispersion of kaolin was prepared by mixing 96 g of water and 4 g of kaolin at 6500 rpm for 30 seconds using a homogenizer (IKA, Ultra-turrax).
[0163] Sodium bicarbonate (SBC) was then added and mixed in an amount of 0.1 parts by weight based on 100 parts by weight of acrylic acid, and just before initiating polymerization, 0.12 g of hydrogen peroxide (H2O2), 0.04 g of ascorbic acid and 2 g of sodium persulfate were added to prepare a monomer composition for preparing a superabsorbent polymer.
[0164] A super absorbent polymer was prepared by the same method as in Comparative Example 1 (2) using the monomer composition.
[0165] Example 2
[0166] A monomer composition for preparing a super absorbent polymer and a super absorbent polymer were prepared by the same method as in Example 1, except that kaolin (average particle size (D50) of 0.6 μm) was added in an amount of 0.5 parts by weight based on 100 parts by weight of acrylic acid.
[0167] Example 3
[0168] A monomer composition for preparing a super absorbent polymer and a super absorbent polymer were prepared by the same method as in Example 1, except that kaolin (average particle size (D50) of 0.6 μm) was added in an amount of 1 part by weight based on 100 parts by weight of acrylic acid.
[0169] Example 4
[0170] A monomer composition for preparing a super absorbent polymer and a super absorbent polymer were prepared by the same method as in Example 1, except that bentonite (average particle size (D50) of 0.8 μm) was added in an amount of 0.25 parts by weight based on 100 parts by weight of acrylic acid.
[0171] Example 5
[0172] A monomer composition for preparing a super absorbent polymer and a super absorbent polymer were prepared by the same method as in Example 1, except that bentonite (average particle size (D50) of 0.8 μm) was added in an amount of 0.5 parts by weight based on 100 parts by weight of acrylic acid.
[0173] Example 6
[0174] A monomer composition for preparing a super absorbent polymer and a super absorbent polymer were prepared by the same method as in Example 1, except that bentonite (average particle size (D50) of 0.8 μm) was added in an amount of 1 part by weight based on 100 parts by weight of acrylic acid.
[0175] Example 7
[0176] In a 3 L glass container equipped with a stirrer and a thermometer, 450 g of acrylic acid, 3 g of PEGDA400 (polyethylene glycol diacrylate 400) internal crosslinking agent, and 0.04 g of diphenyl (2,4,6-trimethylbenzoyl) -phosphine oxide photoinitiator were added and dissolved, and then 580 g of 31.5% sodium hydroxide solution was added to prepare a monomer mixture (neutralization degree: 70 mol%; solid content: 41 wt%).
[0177] In a separate flask, 2 g of polyacrylamide (Merck, polyacrylamide weight average molecular weight: 40000 g / mol), 4 g of montmorillonite (average particle size (D50): 0.8 μm) and 96 g of water were placed and stirred at 6500 rpm for 30 seconds using a homogenizer (IKA, Ultra-turrax) to prepare a 4 wt% clay dispersion.
[0178] A dispersion of clay was added to the monomer mixture so that the content of clay became 0.5 parts by weight based on 100 parts by weight of acrylic acid, 0.1 parts by weight of sodium bicarbonate (SBC) was added and mixed based on 100 parts by weight of acrylic acid, and just before initiating polymerization, 0.12 g of hydrogen peroxide (H2O2), 0.04 g of ascorbic acid and 2 g of sodium persulfate were added to prepare a monomer composition for preparing a super absorbent polymer.
[0179] A super absorbent polymer was prepared by the same method as in Comparative Example 1 (2) using the monomer composition.
[0180] Comparative Example 2
[0181] A super absorbent polymer was prepared by the same method as in Comparative Example 1, except that the polymerization temperature was 50°C.
[0182] Comparative Example 3
[0183] A monomer composition for preparing a super absorbent polymer and a super absorbent polymer were prepared by the same method as in Comparative Example 1, except that 0.12 g of hydrogen peroxide (H2O2) and 0.04 g of ascorbic acid were additionally added when preparing the monomer composition.
[0184] Comparative Example 4
[0185] A monomer composition for preparing a super absorbent polymer and a super absorbent polymer were prepared by the same method as Comparative Example 1, except that when preparing the monomer composition, 0.2 parts by weight of sodium bicarbonate (SBC) as a foaming agent was added based on 100 parts by weight of acrylic acid.
[0186] Comparative Example 5
[0187] A monomer composition for preparing a super absorbent polymer and a super absorbent polymer were prepared by the same method as Comparative Example 1, except that 0.3 parts by weight of sodium bicarbonate (SBC) as a foaming agent was added based on 100 parts by weight of acrylic acid when preparing the monomer composition.
[0188] Comparative Example 6
[0189] A monomer composition for preparing a super absorbent polymer and a super absorbent polymer were prepared by the same method as in Example 2, except that the stirring speed of the homogenizer was set to 300 rpm when mixing the monomer mixture and the aqueous dispersion of kaolin.
[0190] Experimental Example 1: Evaluation of the properties of the monomer composition for preparing superabsorbent polymer
[0191] According to the G' curve and G" curve obtained during the polymerization process of each monomer composition for preparing superabsorbent polymers in the embodiments and comparative examples, the gel point (GP), normalized GP, G' at GP, the final G' of the polymer after the completion of polymerization (final G') and the increase rate of G' from the gel point to the completion of polymerization (ΔG' / s) were calculated, and the results are shown in Table 1 below.
[0192] The gel point is the time (seconds, s) at the intersection of the G' curve and the G" curve, and the normalized gel point is calculated according to the following formula 1.
[0193] [Formula 1]
[0194] Normalized gel point = gel point (seconds) / total polymerization time (seconds)
[0195] Experimental Example 2: Evaluation of properties of superabsorbent polymers
[0196] (1) Vortex time of base resin
[0197] The vortex time of each superabsorbent polymer of Examples and Comparative Examples was measured as follows: For the measurement of the vortex time, a superabsorbent polymer fractionated through a #30-50 sieve was used.
[0198] ① First, in a 100 mL flat-bottom beaker, use a 100 mL measuring cylinder to introduce 50 mL of 0.9% saline.
[0199] ② Next, place the beaker in the center of the magnetic stirrer and place a circular magnet (8 mm in diameter and 30 mm in length) into the beaker.
[0200] ③ Thereafter, the stirrer was operated so that the magnetic bar stirred at 600 rpm and the lowest part of the vortex generated by stirring was brought into contact with the magnetic bar.
[0201] ④ Confirm that the temperature of the saline in the beaker becomes 24.0°C, then introduce 2±0.01 g of the superabsorbent polymer sample while operating a stopwatch to measure the time until the vortex disappears and the liquid surface becomes completely horizontal, which is designated as the vortex time.
[0202] (2) Centrifugal retention capacity (CRC)
[0203] Centrifuge retention capacity (CRC) was measured according to the European Disposables and Nonwovens Association (EDANA) standard EDANA WSP241.3. Superabsorbent polymer of W0 (g, about 0.2g) was evenly placed in a sleeve made of nonwoven fabric, and the sleeve was sealed, and then the sleeve was immersed in a saline solution (0.9 wt % sodium chloride aqueous solution). After 30 minutes, the sleeve was drained at 250G for 3 minutes using a centrifuge, and then the weight W2 (g) of the sleeve was measured. At the same time, the same operation was performed without using superabsorbent polymer, and then the weight W1 (g) at this time was measured. Using the weight thus obtained, CRC (g / g) was calculated according to the following calculation formula 2 to confirm the centrifuge retention capacity.
[0204] [Calculation formula 2]
[0205] CRC(g / g)={[W2(g)-W1(g)-W0(g)] / W0(g)}
[0206] (3) Absorption under pressure (AUP)
[0207] For the superabsorbent polymers prepared in Examples and Comparative Examples, the absorbency under pressure (AUP) was measured according to the method of European Disposables and Nonwovens Association Standard EDANA WSP242.3-10.
[0208] First, a 400-mesh stainless steel wire mesh is installed at the bottom of a plastic cylinder with an inner diameter of 60 mm. Then, at a temperature of 23±2°C and a humidity of 45%, W0 (g, about 0.90 g) of each superabsorbent polymer obtained in the embodiment and the comparative example is evenly sprinkled on the wire mesh, and a piston capable of evenly applying a load of 4.83 kPa (0.7 psi) is added, wherein the outer diameter of the piston is slightly less than 60 mm, there is no gap with the inner wall of the cylinder, and the up and down movement is not hindered. At this time, the weight of the measuring device is W3 (g).
[0209] In a petri dish with a diameter of 150 mm, a glass filter with a diameter of 125 mm and a thickness of 5 mm was placed, and a saline solution of 0.90 wt% sodium chloride was poured to the same level as the upper side of the glass filter. And, the above device was placed on the glass filter and the liquid was absorbed under load for 1 hour. After 1 hour, the measuring device was lifted and the weight W4 (g) was measured.
[0210] Using the measured weight, AUP (g / g) was calculated according to the following calculation formula 3 to confirm the pressure absorption rate.
[0211] [Calculation formula 3]
[0212] AUP(g / g)=[W4(g)-W3(g)] / W0(g)
[0213] In formula 3,
[0214] W0 (g) is the initial weight of the superabsorbent polymer (g),
[0215] W3(g) is the sum of the weight of the superabsorbent polymer and the weight of the device capable of applying a load to the superabsorbent polymer, and
[0216] W4(g) is the sum of the weight of the superabsorbent polymer and the weight of a device capable of applying a load to the superabsorbent polymer after absorbing a saline solution in the superabsorbent polymer under a load (0.7 psi) for 1 hour.
[0217] (3) Saline Flow Conductivity (SFC)
[0218] Measured and calculated according to the method disclosed in columns 54 to 59 of registered patent US5562646.
[0219] (4)T20
[0220] 9g of sodium chloride and 0.1g of Lorodac (main component: linear C12-14 alcohol ethoxylate, CAS#68439-50-9) were dissolved in 1L of distilled water to form an aqueous solution, and the time taken for 1g of superabsorbent polymer to absorb 20g of the aqueous solution under a load of 0.3psi was calculated and measured. The specific measurement method of T20 is described in detail on pages 13 to 18 of the published patent EP2535027.
[0221] (5) Performance Index (PI)
[0222] The CRC (g / g), AUP (g / g), SFC (·10 -7 cm 3 ·s / g) and T20 (seconds), and the performance index (PI, no unit) was calculated by the following calculation formula 1.
[0223] [Calculation formula 1]
[0224] Performance index (PI) = (CRC / 27) + (AUP / 24) + (SFC / 30) - (T20 / 140)
[0225] The results are shown in Table 2 below.
[0226] [Table 1]
[0227]
[0228] *Parts by weight based on 100 parts by weight of acrylic acid [Table 2]
[0229]
Claims
1. A monomer composition for preparing a superabsorbent polymer, comprising: an acrylic monomer having an acidic group at least part of which is neutralized; a crosslinking agent; clay; a carbonate foaming agent; and a polymerization initiator, in, When the monomer composition for preparing a super absorbent polymer is irradiated with heat and / or light to perform a polymerization reaction, a normalized gel point represented by the following Formula 1 is 0.01 to 0.1: [Formula 1] Normalized gel point = gel point (seconds) / total polymerization time (seconds) In Formula 1, the gel point is the polymerization time at the intersection of a storage modulus graph of the monomer composition for preparing the super absorbent polymer according to polymerization time and a loss modulus graph of the monomer composition for preparing the super absorbent polymer according to polymerization time.
2. The monomer composition for preparing a superabsorbent polymer according to claim 1, wherein When the monomer composition for producing a super absorbent polymer is irradiated with heat and / or light to perform a polymerization reaction, the rate of increase of the gel strength from the gel point to the completion of the polymerization is 210 Pa / s or more.
3. The monomer composition for preparing a superabsorbent polymer according to claim 1 or 2, wherein: The clay may be included in an amount of about 0.1 parts by weight to about 5 parts by weight based on about 100 parts by weight of the acrylic monomer.
4. The monomer composition for preparing a superabsorbent polymer according to any one of claims 1 to 3, wherein The average particle size of the clay is 0.025 μm to 10 μm.
5. The monomer composition for preparing a superabsorbent polymer according to any one of claims 1 to 4, wherein The surface of the clay is modified with a polymer dispersant including two or more functional groups selected from the group consisting of an amine group, a carbonyl group, and a hydroxyl group.
6. The monomer composition for preparing a superabsorbent polymer according to claim 5, wherein: The polymer dispersant is one or more selected from the group consisting of polyvinyl pyrrolidone, polyacrylamide and polyacrylic acid.
7. A method for preparing the monomer composition for preparing a superabsorbent polymer according to claim 1, comprising the following steps: an acrylic monomer having an acidic group at least a portion of which is neutralized; a crosslinking agent; and a carbonate foaming agent; and a polymerization initiator, and Clay was added to the mixture obtained in the previous step and shear mixed at a stirring speed of more than 6500 rpm.
8. A polymer prepared from the monomer composition for preparing a superabsorbent polymer according to claim 1, wherein: When the water content is 40 wt % to 80 wt %, the gel strength is 35000 Pa to 60000 Pa.
9. A superabsorbent polymer prepared from the monomer composition for preparing a superabsorbent polymer according to claim 1, wherein: The performance index (PI) represented by the following calculation formula 1 is 2.35 or more, and T20 is less than 190 seconds: [Calculation formula 1] Performance index (PI) = (CRC / 27) + (AUP / 24) + (SFC / 30) - (T20 / 140) In formula 1, CRC is the centrifugal retention capacity (g / g) of a superabsorbent polymer for a 0.9 wt % sodium chloride aqueous solution for 30 minutes. AUP is the absorption rate (g / g) of a superabsorbent polymer for a 0.9 wt% sodium chloride aqueous solution under a pressure of 0.7 psi for 1 hour. SFC is the saline conductivity of 0.685 wt% sodium chloride aqueous solution (·10 -7 cm 3 s / g), and T20 is the time (seconds) it takes for 1 g of superabsorbent polymer to absorb 20 g of an aqueous solution of C12-14 alcohol ethoxylate at 0.3 psi.
10. A method for preparing a superabsorbent polymer, comprising the following steps: irradiating the monomer composition for preparing a superabsorbent polymer according to claim 1 with heat and / or light to polymerize it, thereby preparing a hydrogel polymer; drying, grinding and classifying the hydrogel polymer to form a base resin; as well as A surface cross-linked layer is formed on the surface of the base resin in the presence of a surface cross-linking solution including a surface cross-linking agent and a solvent.
Citation Information
Patent Citations
Biomarker for diagnosing atopic dermatitis and use thereof
KR1020230028619A
Apparatus and method for operating two-wheeler trade
KR1020240030792A